Müllerian duct anomaly with congenital rectovaginal fistula: A rare case presentation - Yogita Dogra; Santosh Minhas; Poojan Marwaha (South African Medical Association, 2015)
Pregnancy in a rudimentary horn is a rare form of ectopic gestation and associated with high maternal mortality. Unicornuate uterus with a rudimentary horn is caused by disordered fusion of Müllerian ducts during embryonic life, which can be associated with ipsilateral renal agenesis, congenital rectovaginal fistula, imperforate anus, hypospadias and other anatomical variants of cloacal dysgenesis. Despite advances in imaging techniques such as ultrasound, the diagnosis of rudimentary horn remains elusive with confirmatory diagnosis made on laparotomy. Our patient presented with an unruptured rudimentary horn pregnancy in the second trimester with a past history of surgical correction of rectovaginal fistula. Exploratory laparotomy was done and the rudimentary horn was excised. We report this case because of the very rare association of unicornuate uterus with rudimentary horn with congenital rectovaginal fistula, which forms when the Müllerian eminence opens in the dorsal segment of the endodermal cloaca.